Acute effect of caffeine supplementation on 100-m sprint running performance: a field test - Matsumura, T.; Tomoo, K.; Sugimoto, T.; tsukamoto, H.; Shinohara, Y.; Otsuka, M.; Hashimoto, T. (Medicine & Science in Sports & Exercise, 2023)
Purpose No study has assessed the acute effect of caffeine supplementation on 100-m sprint running in athletics and caffeine`s net ergogenicity on 100-m sprint running remains unclear. We investigated the acute effects of caffeine supplementation on 100-m sprint running performance in a field test.